2019
DOI: 10.3847/1538-4365/ab42da
|View full text |Cite
|
Sign up to set email alerts
|

Automated Mining of the ALMA Archive in the COSMOS Field (A3COSMOS). I. Robust ALMA Continuum Photometry Catalogs and Stellar Mass and Star Formation Properties for ∼700 Galaxies at z = 0.5–6

Abstract: The rich information on (sub-)millimeter dust continuum emission from distant galaxies in the public Atacama Large Millimeter/submillimeter Array (ALMA) archive is contained in thousands of inhomogeneous observations from individual PI-led programs. To increase the usability of these data for studies deepening our understanding of galaxy evolution, we have developed automated mining pipelines for the ALMA archive in the COSMOS field (A3COSMOS) which efficiently exploit the available information for large numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 180 publications
(401 reference statements)
2
65
0
Order By: Relevance
“…We have analysed the IRX-β/M * dust attenuation relations of star forming galaxies at z ∼ 2.5 − 4.0 using all the publicly available ALMA archival data in the COSMOS field. In particular, we include all primary targeted galaxies as well as serendipitously covered sources within the primary beam width of existing ALMA continuum images that were processed by the A 3 COSMOS project team (Liu et al 2019). The ALMA data were cross-matched with the COS-MOS2015 optical-NIR photometric catalogue (Laigle et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We have analysed the IRX-β/M * dust attenuation relations of star forming galaxies at z ∼ 2.5 − 4.0 using all the publicly available ALMA archival data in the COSMOS field. In particular, we include all primary targeted galaxies as well as serendipitously covered sources within the primary beam width of existing ALMA continuum images that were processed by the A 3 COSMOS project team (Liu et al 2019). The ALMA data were cross-matched with the COS-MOS2015 optical-NIR photometric catalogue (Laigle et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The previously derived IRX-M relations up to z ∼ 4 are mostly consistent with each other, and thus several studies agree on the nonevolution of the IRX-M relation over a wide redshift range. However, in a recent study, Fudamoto et al (2020) found a significantly steeper IRX-M relation using an unbiased sample of star forming galaxies at z ∼ 3 by exploring the entire public ALMA archive data in COSMOS (A 3 COSMOS, Liu et al 2019). The steeper slope in Fudamoto et al (2020) could reflect a difference in the FIR SED used in previous studies and/or a potential measurement bias in previous stacking analyses, which relied on low-resolution data (e.g., Herschel), however the exact reason is not yet clear.…”
Section: Irx-m Relationmentioning
confidence: 99%
“…This is related to the ability of recovering low surface brightness emission. Extensive simulations on this aspect have been reported in Liu et al (2019), who presented a generic simulation. This is non-trivial to assess.…”
Section: Comparison To the S 3 -Sex Semi-empirical Simulationmentioning
confidence: 99%